Education in Methodology for Health Care – EuroMISE - Zvárová, J. (Methods of Information in Medicine, 1994)
In January 1993 the Joint European Project “Education in the methodology field of health care”, EuroMISE (European Education in Medical Informatics, Statistics and Epidemiology) started under the European TEMPUS program. Training and education in EuroMISE consist of three overlapping methodology branches: medical informatics, medical statistics, and epidemiology. A teaching scheme has been developed in cooperation between Charles University, Prague, and EC universities and organizations involved in the EuroMISE project. One of the main tasks of the project is to design a modularly structured EuroMISE course set, to develop teaching materials and tools in the English language, and to link the EuroMISE project with other programs and projects in this field. Running EuroMISE courses, firstly for university teachers, will have a major impact in disseminating the acquired knowledge and skills.
Keywords: Medical Informatics; Medical Statistics; Epidemiology; Curriculum; Education; EuroMISE